If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 17 = 12 Reorder the terms: 17 + 5a = 12 Solving 17 + 5a = 12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 5a = 12 + -17 Combine like terms: 17 + -17 = 0 0 + 5a = 12 + -17 5a = 12 + -17 Combine like terms: 12 + -17 = -5 5a = -5 Divide each side by '5'. a = -1 Simplifying a = -1
| 9/7n=30 | | 7/5x=21 | | .13-01(x+1)=-.03(4-x) | | 2(6-6x)+7(x-7)=Ax+B | | 14/3+1/5t=7 | | 3(5x+6)=-12+15 | | 0=x^2-14x+24 | | 6u^3(-2u^5)= | | 0=8h^2+12h-4896 | | y=2x^2-x+2 | | 3x(x-9)=13x^2-28x | | 1=15t-5t^2 | | 3.6q-1.2-4.1q=-1.5q-5.1 | | (x^2+12x)+(3x^2+20)=180 | | 6w=3P-6l | | 9xsquared+4=12x | | 0=x^2-12x+11 | | 8(t-4)+4t=4(3t+3)-9 | | 7h+2h-5=19 | | 8x-4=5x+1 | | y=k(x-a)(x-b) | | 3+4x=2(2x+2) | | 4x^2+12X=160 | | -5y+6=-8y+12 | | 1.001/7=b | | x+x+17+2(x-30)=695 | | 11x+36=6x+6 | | 4/3*(3.14)*10^3 | | x+10x+25(33-2x)=182 | | 9xy-2y=-5 | | 11x-7+2x-3=10x-3+2x | | 2x-5+(3x+4)=5x-1 |